AWJM parametric investigation on hybrid composite produced through two step stir casting process. (21st August 2019) - Ganesan, P; Vinoth Babu, K; S, Suresh Kumar; Marichamy, S; Madan, D
Abstract: Abrasive Water Jet Machining (AWJM) is well known non-traditional machining process employed to machine difficult to cut materials with complex contours. The proposed research work deals with the machinability investigation of AA-2024-B4 C-TiC hybrid composite through AWJM process. The machining characteristics as output responses for the analysis are Surface Roughness (SR), Material Removal Rate (MRR) and Kerf angle (KA). The effect of individual process parameters are water Jet Pressure (JP), Standoff Distance (SOD) and Traverse Speed (TS), these parameters holds higher degree of influence over output responses. The influence analysis shows the notable increment in the metal removal process with the increased SOD, TS and water pressure. Moreover, the optimal combination of process parameters and their contribution are determined through Grey Relational Analysis (GRA). The optimum parameters obtained from GRA are water jet pressure of 260 bar, stand-off distance at 1 mm and traverse speed of 20 mm min −1 . Moreover, the most significant factor on affecting the responses were water jet pressure (82.17%) followed by the transverse speed (13.84%)